Percutaneous cystolithotomy in augmented bladders - Uday Sankar Chatterjee; Indranil Chatterjee (Wolters Kluwer Medknow Publications, 2021)
Aims: Incidence and recurrence of bladder stone in augmented exstrophy bladder rate is high. So, recurrent open cystolithotomy is not a preferred procedure; particularly through scarred tissues, consequence of previous surgeries. Percutaneous cystolithotomy (PCCL) is an old but standard procedure for retrieval of bladder stones in adults. We extrapolated PCCL for bladder stone in augmented bladders in children. Patients and Methods: In three patients, we made suprapubic (SP) needle track with initial puncture (IP) needle under cystoscopic guidance. Following that laparoscopic cannula was placed through dilated SP track that was crafted with Alken's dilators and bladder stones were removed with grasper. Results: On cystoscopy, we also observed the patches of skin tissues in native bladders. Continence and bladder capacity were not affected following PCCL. Conclusion: PCCL in augmented bladder showed good outcome. High recurrence of bladder stone is possibly due to presence of keratin in dermal tissue; invaded mucosa in open bladder plate. It seems shaving or fulguration of those dermal elements during bladder reconstruction might decrease incidence of stone formation. However, we haven't attempted fulguration during PCCL.